Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The PDF (it's small) is available here:

It says:

1 ≡ −332×79 mod 1249

Equivalently, since:

−332≡(1249−332) mod1249

How did they get that equivalency? How do you jump from that first equation to the next?

share|cite|improve this question
up vote 3 down vote accepted

You are reading it incorrectly, what it says the following.

$$\color{red}{1 \equiv -332 \times 79 \pmod{1249}\\ \text{Equivalently} \\ 1 \equiv 917 \times 79 \pmod{1249}}$$

To prove that the two statements are equivalent, it uses the fact that $$-332 \equiv (1249-332) \pmod{1249} \equiv 917 \pmod{1249}$$

share|cite|improve this answer
How am I reading it wrong? I copy and pasted what it says. – Doug Smith Dec 16 '12 at 5:15
@DougSmith The statements $$-332 \equiv (1249-332) \pmod{1249} \equiv 917 \pmod{1249}$$ are intermediate statements and the actual equivalent statements are $$\color{red}{1 \equiv -332 \times 79 \pmod{1249}\\ \text{Equivalently} \\ 1 \equiv 917 \times 79 \pmod{1249}}$$ – user17762 Dec 16 '12 at 5:17

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.